Synergy of Teachers, Parents, and the Community in Anticipating the Use of Illegal Drugs Among MTsN Students in South Banjarmasin District - Suraijiah, Suraijiah; Aisyah, Siti (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
The synergy between teachers, parents, and the community in anticipating drug abuse in MTsN 3, MTsN 4, and MTsN 1 is going well, but these anticipatory efforts must continue to be strengthened. Drug abuse is a serious violation that has a negative impact on the future of the younger generation. The three educational institutions have taken the right steps, such as working with parents to supervise their children and providing an understanding of the dangers of drugs, both through direct meetings and online media. In addition, the school also collaborates with the Police, BNN, and Health Centers to provide counseling on the negative impacts of drug abuse. These efforts have succeeded in reducing, even eliminating cases of drug abuse in both schools for quite a long time. However, the synergy between schools, families, and the community must continue to be strengthened. Supporting factors include cooperation with competent parties and parental awareness, while obstacles include the influence of social media and lack of parental supervision of children's socializing outside of school.